Health-Related Quality of Life in Children With Earlier Surgical Repair for Right Ventricular Outflow Tract Anomalies and the Agreement Between Children and Their Parents - Svensson, Birgitta; Idvall, Ewa; Nilsson, Fredrik; Liuba, Petru (Frontiers in Cardiovascular Medicine, 2020)
Background: Children diagnosed with right ventricle outflow tract (RVOT) anomalies require surgical repair early in life, reoperations and lifelong follow-up. The aim is to comprehensively describe their health related quality of life (HRQoL) and to assess the agreement in this regard between children and parents. Methods and Results: Child- and parent-reported HRQoL was assessed in 97 children aged 8–18 years using three different HRQoL questionnaires. The mean age was 12.9 ± 3 years. The mean total score for the child report was lower in the PedsQL Cardiac Module than in the PedsQL 4.0 and DISABKIDS (p ≤ 0.001). The mean score for each domain in PedsQL Cardiac Module ranged between 67 (cognitive function) and 79 (physical appearance), and between 72 (school function) and 82 (physical and social function) in PedsQL 4.0. Nearly half of the children reported problems with shortness of breath during physical activity. In the PedsQL Cardiac Module the child-parent agreement was strong for 13 of 22 items. Conclusion: HRQoL problems as perceived by children with RVOT anomalies are best identified with the PedsQL Cardiac Module and relate mostly to cognitive and physical functioning. The agreement findings suggest the need to take into account both child- and parent reports in the assessment of HRQoL.